Interdependence in rainwater management technologies: an analysis of rainwater management adoption in the Blue Nile Basin - Gebregziabher, Gebrehaweria; Rebelo, Lisa-Maria; Langan, Simon J. (Springer, 2016)
In the Blue Nile Basin of Ethiopian highlands, rainfall distribution is extremely uneven both spatially and temporally. Drought frequently results in crop failure, while high rainfall intensities result in low infiltration and high runoff causing soil erosion and land degradation. These combined factors contribute to low agricultural productivity and high levels of food insecurity. Poor land management practices coupled with lack of effective rainwater management strategies aggravate the situation. Over the past two decades, however, the Government of Ethiopia has attempted to address many of these issues through a large-scale implementation of a number of soil and water conservation measures. Despite the success of interventions, uptake and adoption remains low. The conceptual framework of this study is based on the premise that farmers are more likely to adopt a combination of rainwater management technologies as adaptation mechanism against climate variability and agricultural production constraints. This contrasts the previous work that typically examined a single technology without considering the interdependence between technologies. Data used in this study come from household survey in seven watersheds in the Ethiopian Blue Nile Basin. A multivariate probit model was used to account for the potential correlation and interdependence of various components of rainwater management technologies. Our results suggest that rainwater management technologies are related with each other; hence, any effort to promote the adoption of rainwater management technologies has to consider such interdependence of technologies, or failure to do so may mask the reality that farmers face a set of choices in their adoption decisions.